A Study on Impact of Digital Currency on Stakeholders - Poojari, Lata; Sandanshive, Dr. Vishal Rajendra; Singh, Dr. Rekha; Natu, Dr. Pankaj (The journal of contemporary issues in business and government, 2022)
Central Bank Digital Currency (CBDC) is a digital form of currency notes issued by a central bank. While most central banks across the globe are exploring the issuance of CBDC, the key drives for its issuance are specific to each country’s and concentrate on the exclusive requirements. In the Union Budget 2022-23, Finance Minister of India Mrs. Nirmala Sitharaman had announced about RBI rolling out a digital equivalent to the rupee in the current financial year (2022). The research paper aims to study and understand the significance of Digital Currency and its prospective impact on various stakeholders such as retail customers, corporate customers, domestic banks, international banks, fin-tech solution providers and especially central banks operations and processes. The present study is descriptive in nature and based on secondary data.